The aid effect : giving and governing in international development. - Mosse, David; Lewis, David J. (Anthropology, culture and society, 2005)
Today international development policy is converging around ideas of neoliberal reform, democratisation and poverty reduction. What does this mean for the local and international dimensions of aid relationships? The Aid Effect demonstrates the fruitfulness of an ethnographic approach to aid, policy reform and global governance. The contributors provide powerful commentary on hidden processes, multiple perspectives or regional interests behind official aid policy discourses. The book raises important questions concerning the systematic social effects of aid relationships, the nature of sovereignty and the state, and the working of power inequalities built through the standardisations of a neoliberal framework.